HGF and IGF‐1 promote protective effects of allogeneic BMSC transplantation in rabbit model of acute myocardial infarction. (15th October 2015) - Zhang, Guang‐Wei; Gu, Tian‐Xiang; Guan, Xiao‐Yu; Sun, Xue‐Jun; Qi, Xun; Li, Xue‐Yuan; Wang, Xiao‐Bing; Lv, Feng; Yu, Lei; Jiang, Da‐Qing; Tang, Rui
Abstract: Objectives: To explore effects of hepatocyte growth factor (HGF) combined with insulin‐like growth factor 1 (IGF‐1) on transplanted bone marrow mesenchymal stem cells (BMSCs), for treatment of acute myocardial ischaemia. Materials and methods: After ligation of the left anterior descending artery, rabbits were divided into a Control group, a Factors group (HGF+IGF‐1), a BMSC group and a Factors+BMSCs group. Allogenous BMSCs (1 × 10 7 ) and/or control‐released microspheres of 2 μg HGF+2 μg IGF‐1 were intramyocardially injected into infarcted regions. Apoptosis and differentiation of implanted BMSCs, histological and morphological results, and cardiac remodelling and function were evaluated at different time points. In vitro, BMSCs were exposed to HGF, IGF‐1 and both (50 ng/ml) and subsequently proliferation, migration, myocardial differentiation and apoptosis induced by hypoxia, were analysed. Results: Four weeks post‐operatively, the above indices were significantly improved in Factors+BMSCs group compared to the others ( P < 0.01), although Factors and BMSCs group also showed better results than Control group ( P < 0.05). In vitro, HGF promoted BMSC migration and differentiation into cardiomyocytes, but inhibited proliferation ( P < 0.05), while IGF‐1 increased proliferation and migration, and inhibited apoptosis induced by hypoxia ( P < 0.05), but did not induce myocardial differentiation. Combination of HGF and IGF‐1 significantly promoted BMSCs capacity for migration, differentiation and lack of apoptosis ( P < 0.05). Conclusions: Combination of HGF and IGF‐1 activated BMSCs complementarily, and controlled release of the two factors promoted protective potential of transplanted BMSCs to repair infarcted myocardium. This suggests a new strategy for cell therapies to overcome acute ischemic myocardial injury.